Two-stage Heuristic Method for Primary School Timetabling Problem with Considerations for Combined-classes - Tan, See Yan (Universiti Malaysia Sarawak (UNIMAS), 2019)
This research focuses on a primary school timetabling problem, a small-scale primary school that is located at Pengerang, Johor. In this small-scale primary school six classes have been allotted for standard one to standard six. Most of the primary schools timetable are manually developed, which is extremely time consuming. According to the new policy announced on 12th December 2017 by the Ministry of Education (MoE) Malaysia, due to the shortage of teachers, combined-classes policy should be implemented at low-enrollment schools. MoE has introduced another policy on 30th June 2018 that recommends schools to reduce the number of subjects that are being taught in a day in order to solve the overloaded school bag issue. There is a set of hard constraints in this primary school timetabling problem due to the stipulation that a teacher can only teach one subject at a time; each subject must satisfy the total weekly period(s) and the combined-classes can only combine one subject at a time. The main objective of this study is to propose a computational bounded heuristic solution to solve primary school timetabling problem with the consideration of combined-classes. A two-stage timetabling heuristic has been proposed due to its simplicity to cope with the numerous constraints. The two-stage heuristic method clusters subjects into subject groups at the first stage to ease the timeslots allocation at the second stage. The subjects with no common teachers will be assigned into a subject group. Timeslots allocation stage allocates the subject group into available timeslots with condition considerations. Based on the results generated, the proposed heuristic approach produced a clash-free timetable which met the constraints within a few seconds. Improvement of spreading the teaching slot evenly and decreasing the number of subjects taught in a day to reduce an overloaded bag were achieved. A timetable that has been generated by this proposed solution outperforms the current manual practice.